2004
DOI: 10.1017/s0022029904000433
|View full text |Cite
|
Sign up to set email alerts
|

Decision tree analysis to evaluate dry cow strategies under UK conditions

Abstract: Economic decisions on animal health strategies address the cost benefit aspect along with animal welfare and public health concerns. Using decision tree analysis at an individual cow level has highlighted that there is little economic difference between the use of either dry cow antibiotic or an internal teat sealant compared with no treatmnet in preventing a new intra mammary infection in a cow free of infection in all quarters of the mammary gland at drying off.However, a potential net loss of over £20 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
0
30
1
Order By: Relevance
“…The previous reports stated that the DCT with antibiotics prevented infections, which occur in the first trimester of lactation (5). Conversely, in this study antibiotic treatment alone was not found to be preventive against new infections occurring in the dry period.…”
Section: Discussioncontrasting
confidence: 51%
“…The previous reports stated that the DCT with antibiotics prevented infections, which occur in the first trimester of lactation (5). Conversely, in this study antibiotic treatment alone was not found to be preventive against new infections occurring in the dry period.…”
Section: Discussioncontrasting
confidence: 51%
“…It is presumable that peak milk concentration in tylosin treated animals was higher than previously reported, therefore achieving bactericidal activity, which was observed for macrolides when used in high concentrations (14). In conclusion, DCT remains a cost-effective measure compared with no treatment at dryoff (3,16,17). The use of systemic tylosin in combination with the intramammary cephapirin increased the effectiveness of intramammary DCT against Gram-positive IMI.…”
Section: Resultsmentioning
confidence: 83%
“…The costs of involuntary culling differ over time, depending on milk production, parity, lactation stage and reproductive status (20). with the economic profit of dry cow treatment (DCT) (6), and one with the economic profit of vaccination against clinical E. coli mastitis (7) ( MPV was calculated by multiplying the average milk price by the marginal products (increased revenues) of using a specific control procedure.…”
Section: Cullingmentioning
confidence: 99%